The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/bcr.0000000000000313
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Inhalation Injury Diagnostic Methods and Patient Outcomes

Abstract: The purpose of this study was to compare patient outcomes according to the method of diagnosing burn inhalation injury. After approval from the American Burn Association, the National Burn Repository Dataset Version 8.0 was queried for patients with a diagnosis of burn inhalation injury. Subgroups were analyzed by diagnostic method as defined by the National Burn Repository. All diagnostic methods listed for each patient were included, comparing mortality, hospital days, intensive care unit (ICU) days, and ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The initial laboratory analyses in patients with burn a size of ≥15%TBSA include complete blood count, electrolyte assessment, coagulation profile and arterial blood gas measurement. In patients with suspected smoke inhalation injury, normal oxygenation and chest radiographs do not rule out the diagnosis as the pulmonary inflammatory response may take time to develop 110,111 .…”
Section: Secondary Surveymentioning
confidence: 99%
“…The initial laboratory analyses in patients with burn a size of ≥15%TBSA include complete blood count, electrolyte assessment, coagulation profile and arterial blood gas measurement. In patients with suspected smoke inhalation injury, normal oxygenation and chest radiographs do not rule out the diagnosis as the pulmonary inflammatory response may take time to develop 110,111 .…”
Section: Secondary Surveymentioning
confidence: 99%
“…Our results showed that overall, 30-day in-hospital and inhalation injury mortality rates of 9.6% and 15.8%, respectively, were lower than described in previous literature. 19,21,27,28 Mortality is also highly associated with progressing ARDS severity, with rates as high as 50% reported in patients with P:F ratio less than 100 within the first seven days of admission. 20 Our patient sample displayed in-hospital mortality rates of 18.2% (Table 3) for severe ARDS, with an incidence of 2.4% (Figure 1) by hospital day seven.…”
Section: Discussionmentioning
confidence: 99%
“…In this study bronchoscopy proved useful in predicting mortality, days of ventilation and duration of intensive care unit (ICU) admission. 11 Therefore bronchoscopy may have the advantage of securing the diagnosis while simultaneously allowing severity assessment (Table 1) and facilitating bronchial toilet and specimen collection. 12 Helical computed tomography (CT) can effectively evaluate airway wall thickness and airway-lumen dimensions in asthma and chronic obstructive pulmonary disease.…”
Section: Diagnosismentioning
confidence: 99%